A literature review on leaching and recovery of vanadium. Issue 5 (October 2019) - Peng, Hao
Abstract: Vanadium as an important national strategy resource is widely used in many fields due to its excellent physicochemical properties. Much attention had been focused on recovering vanadium from vanadium titano-magnetite and stone coal as they were the main vanadium resources in China. Sodium roasting technology was the earliest technology applied in recovering vanadium, high recovery efficiency of vanadium was obtained along with serious environment problem like corrosive gases and hazardous wastewater. Calcium roasting technology avoided above problems, but high energy-cost and low recovery was remained. Non-salt roasting technology was suitable for limited vanadium resource. Vanadium was leached out after roasting and the leaching medium was divided into three parts according to the roasting technology. Recover process of vanadium depended on the vanadium species and pH in the leaching solution. Hydrolysis was the easily technology with most impurities. Ammonium precipitation was the common process for every technology. And high purity of V2 O5 was obtained by calcining precipitation of recovery process. Overall, the industry of vanadium leaching was still underdeveloped, and much intensive research work was needed.